The Significance of Peaceful Values in Global Perspective: Challenges and Hopes - Azhar Arsyad (TSAQAFAH, 2016)
The paper talks about how violence and conflict in every form of life will get anybody nowhere and how the call for peace and tranquility should be implemented by each mankind, wherever he lives and wherever they as a group may reside. Hence, peaceful values in global perspective are of great significance. The questions which may be raised are what do we need to have and what do we need to know prior to talking about peace and tranquility? The other questions which may spur are how to implement peace and what makes peace fail and tranquility never becomes a reality. The answer to those questions will become an elaboration of the gist of this article. Historically and spiritually speaking, peace will not be realized if the reason of failure to achieve peace has not been made aware and known to mankind. Albeit various advices and directions have been given, peace shall not be realized. This is due to the fact that the advice and directions given have not met the substance of the cause and have not been able to provide a comprehensive solution to peace itself. Some of the substances of this article, therefore, will try to prove how the need to recognizing and understanding the “voice of the heart” as “inner-soul” and “inner capacity” themselves will become an essential thing to be realized by every individual, so that they can thereafter be known by all mankind globally wherever they may be.